Assessment of inoculation methods in evaluating response of yam cultivars to infection by Scutellonema bradys - Baimey, H.; Coyne, Danny L.; Labuschagne, N. (Brill, 2005)
Two glasshouse experiments were conducted to assess the influence of three inoculation methods on Scutellonema bradys multiplication on yam (Dioscorea spp.) and on growth and production of the crop. Three separate cultivars of yam were used in the study: two Dioscorea rotundata cultivars (Ala and Kpouna) and one Dioscorea cayenensis (Tabane). One-month-old plants were each inoculated with approximately 1000 S. bradys juveniles and adults. The inoculation methods included inoculation with chopped infected pieces of yam peel (about 0.5 × 0.3 cm2), chopped and blended infected yam peel and a water suspension (200 ml) of extracted nematodes compared with a S. bradys-free yam tuber peel control. The two experiments were harvested at 9 and 4 months after planting. Nematode population densities at harvest were significantly different (P ≤ 0.05) among inoculation methods and among yam cultivars. Higher nematode population densities were recorded on tubers from plants inoculated with unblended peel, followed by those inoculated with blended peel. Inoculation with nematode suspensions yielded the lowest nematode population densities. Inoculation with S. bradys did not affect the vine circumference and the number of tubers. Weights of tubers differed among inoculation methods for two of the three yam cultivars tested (P ≤ 0.05).